DERIVATION OF THE ANGLE COSINE FORMULAS VIA LAGRANGE’S THEOREM (FOR POLAR SPHERICAL TRIANGLES) - Caritá, Lucas Antonio; Dos Santos, Carla Patrícia Ferreira [UNESP] (My University, 2023)
In the context of Spherical Trigonometry, this study presents an alternative proof for the Angle Cosine Formulas, using the Langrange’s Theorem as support. This text is a continuation of the article [1].
Keywords: Angle Cosine Formulas; Lagrange’s Theorem; Spherical Geometry; Spherical Trigonometry